2023
DOI: 10.1097/aog.0000000000005107
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Malignancy After Atypical Findings on Single-Nucleotide Polymorphism–Based Prenatal Cell-Free DNA Screening

Abstract: To evaluate the incidence and clinical outcomes of cell-free DNA results suspicious for maternal malignancy on prenatal cell-free DNA screening with single-nucleotide polymorphism (SNP)-based technology. METHODS:This retrospective cohort study included data from SNP-based, noninvasive prenatal screening samples from a commercial laboratory from January 2015 to October 2021. Maternal plasma was screened for trisomy 21, 18, and 13; monosomy X; and triploidy. Cases were considered suspicious for maternal malignan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Recent retrospective studies 2,3,7 have reported high rates of cancer detection (67%–73%) in asymptomatic pregnant people when NIPT results were classified as malignancy suspicious, highlighting the importance of facilitating a timely clinical evaluation for pregnant people who receive these results 14 . However, the average amount of time that elapsed between when participants received their NIPT results and enrolled in the IDENTIFY study (the first step to pursuing cancer screening) was 3 months (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent retrospective studies 2,3,7 have reported high rates of cancer detection (67%–73%) in asymptomatic pregnant people when NIPT results were classified as malignancy suspicious, highlighting the importance of facilitating a timely clinical evaluation for pregnant people who receive these results 14 . However, the average amount of time that elapsed between when participants received their NIPT results and enrolled in the IDENTIFY study (the first step to pursuing cancer screening) was 3 months (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, reports of maternal cancer as an explanation for unusual or discordant non-invasive prenatal testing (NIPT) results using cell-free DNA sequencing of maternal plasma have accumulated worldwide, with over 100 cases published. [1][2][3][4][5][6][7] Although these retrospective data demonstrate that NIPT can incidentally detect cancer in asymptomatic pregnant individuals, there is currently limited prospective evidence to inform patient counseling and clinical management of NIPT results that suggest maternal cancer. Consequently, there is no standardized approach to these cases in most countries.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, reports on the identification of a maternal malignancy upon single-nucleotide polymorphism (SNP)-based targeted NIPT technologies are more rare [17]. Yet, given that this method allows distinguishing between maternal and fetal CNAs, it may result in a higher likelihood of detecting a maternal malignancy once a NIPT is found to be suspicious of cancer, as suggested by Goldring et al [17].…”
Section: Routine Nipt Findings Pointing To An Occult Maternal Malignancymentioning
confidence: 99%